Revolutionizing HIV/AIDs Care: Developing a Mobile Application to Enhance Art Adherence Monitoring at Lira City, Northern Uganda. A cross-sectional study. - Alobo, Lucy; Modi , Derick; Musinguzi, Marvin; Ikwara, Emmanuel Asher Ikwara; Nyanzi, Mathias; Nam, Richard; Among, Daphine; Kizza, Daniel (Student’s Journal of Health Research Africa, 2026)
Background: Poor adherence to antiretroviral therapy (ART) remains a major challenge, particularly in Northern Uganda, where social and infrastructural barriers hinder treatment consistency. This study evaluates the effectiveness of an adherence monitoring mobile application at Ober Health Center IV, Lira City, Northern Uganda. Methods. A cross-sectional mixed-methods study was conducted among 35 ART users at Ober Health Center IV. Quantitative data were collected using structured questionnaires, while qualitative insights were obtained through focus group discussions. Statistical associations between adherence and user variables were analyzed using chi-square tests (p < 0.05). Ethical approval and informed consent Consent was obtained before data collection. Results. The majority of participants were aged 18–34 years (80%). Participants diagnosed 4–6 years earlier demonstrated 100% adherence improvement. Overall, 88.6% of participants demonstrated good adherence after using the app. Adherence improvement was significantly associated with duration on ART (p = 0.010), years since diagnosis (p = 0.010*), employment status (p = 0.011*), and preferred app features (p = 0.022*). While app usage frequency was not statistically significant (p = 0.088*), users reported improved motivation, easier dose tracking, and enhanced understanding of ART. Focus group discussions revealed that reminders, consultation, and peer-support features were most valued, although poor internet access and limited phone literacy posed challenges. Conclusion: The adherence monitoring app demonstrated high user acceptability and moderate effectiveness in improving ART adherence in Northern Uganda. Incorporating personalized reminders and interactive features enhanced treatment engagement. Recommendation. Expanding offline functionality and user training could further strengthen its impact and support scale-up across other HIV care settings.